Virulence of Rigidoporus microporus isolates causing white root rot disease on rubber trees (Hevea brasiliensis) in Malaysia - Wen, Ze Go; Chin, Kit Ling; H'ng, Paik San; Wong, Mui Yun; Chuah, Luqman Abdullah; Surendran, Arthy; Tan, Geok Hun; Lee, Chuan Li; Khoo, Pui San; Kong, Wai Jern (MDPI, 2021)
Latex production from Hevea brasiliensis rubber tree is the second most important commodity in Malaysia, but this industry is threatened by the white root rot disease (WRD) caused by Rigidoporus microporus that leads to considerable latex yield loss and tree death. This study aimed to characterize and compare the virulence of five R. microporus isolates obtained from infected rubber trees located at different states in Malaysia. These isolates were subjected to morphological and molecular characterization for species confirmation and pathogenicity test for the determination of virulence level. BLAST search showed that the ITS sequences of all the pathogen isolates were 99% identical to R. microporus isolate SEG (accession number: MG199553) from Malaysia. The pathogenicity test of R. microporus isolates conducted in a nursery with 24 seedlings per isolate showed that isolate RL21 from Sarawak has developed the most severe above- and below-ground symptoms of WRD on the rubber clone RRIM600 as host. Six months after being infected with R. microporus, RL21 was evaluated with the highest average of disease severity index of 80.52% for above- and below-ground symptoms, followed by RL22 (68.65%), RL20 (66.04%), RL26 (54.38%), and RL25 (43.13%). The in vitro growth condition tests showed that isolate RL21 of R. microporus has optimum growth at 25–30 °C, with the preference of weakly acidic to neutral environments (pH 6–7). This study revealed that different virulence levels are possessed among different R. microporus isolates even though they were isolated from the same host species under the same climate region. Taken together, field evaluation through visual observation and laboratory assays have led to screening of the most virulent isolate. Determination of the most virulent isolate in the present study is vital and shall be taken into consideration for the selection of suitable pathogen isolate in the development of more effective control measures in combating tenacious R. microporus.